Women’s Healthcare Utilization Following Routine Screening for Past-Year Intimate Partner Violence in the Veterans Health Administration - Dichter, Melissa E. (J Gen Intern Med, 2018)
BACKGROUND: Experience of intimate partner violence (IPV) can have adverse health impacts and has been associated with elevated rates of healthcare service utilization. Healthcare encounters present opportunities to identify IPV-related concerns and connect patients with services. The Veterans Health Administration (VHA) conducts IPV screening within an integrated healthcare system. OBJECTIVE: The objectives of this study were to compare service utilization in the 6 months following IPV screening between those screening positive and negative for past-year IPV (IPV+, IPV−) and to examine the timing and types of healthcare services accessed among women screening IPV+. DESIGN: A retrospective chart review was conducted for 8888 female VHA patients across 13 VHA facilities who were screened for past-year IPV between April 2014 and April 2016. MAIN MEASURES: Demographic characteristics (age, race, ethnicity, marital status, veteran status), IPV screening response, and healthcare encounters (based on visit identification codes). KEY RESULTS: In the 6 months following routine screening for past-year IPV, patients screening IPV+ were more likely to utilize outpatient care (aOR = 1.85 [CI 1.26, 2.70]), including primary care or psychosocial care, and to have an inpatient stay (aOR = 2.09 [CI 1.23, 3.57]), compared with patients screening IPV−. Among those with any utilization, frequency of outpatient encounters within the 6-month period following screening was higher among those screening IPV+ compared with those screening IPV−. The majority of patients screening positive for past-year IPV returned for an outpatient visit within a brief time frame following the screening visit (> 70% within 14 days, >95% within 6 months). More than one in four patients screening IPV+ had an emergency department visit within the 6 months following screening. CONCLUSIONS: Women who screen positive for past-year IPV have high rates of return to outpatient visits following screening, presenting opportunities for follow-up support. Higher rates of emergency department utilization and inpatient stays among women screening IPV+ may indicate adverse health outcomes related to IPV experience.